(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The purpose of this research is to investigate the landscape of blended learning in the learning environment. It's basically a review paper, in this study more focus is given towards blended learning. This article consisted of various data, which makes this paper more informative. The research overview elaborates on blended learning, demonstrating that from the learner’s perspective, effectiveness outweighs ineffectiveness in learning. This study mentions that online learning, offline learning, and mobile learning modes are engaging for learners. The finding of this study is that blended learning is helpful for many learners, but in some studies it also mentioned that students from different backgrounds are more likely to go with either an online or offline mode of learning. The study’s and review paper’s limitations call for more emphasis on different modes of learning and future research. As a result, more emphasis should be placed on this blended learning research at future.